Signal transduction in human platelets and inflammatory mediator release induced by genetically cloned hemolysin-positive and -negative Escherichia coli strains. - König, B (1990)
Incubation of human platelets with the hemolysin-producing Escherichia coli strain K-12 (pANN5211) induced the activation of protein kinase C, aggregation of platelets, calcium influx, low amounts of 12-hydroxyeicosatetraenoic acid (12-HETE), and release of serotonin from dense granules. Nonhemolytic isogenic strains of E. coli 536/21 which differed only in their types of adhesins (MSH+ MS-Fim+; S-MRH+ S-Fim+; P-MRH+ P-Fim+) released neither serotonin nor 12-HETE from human platelets nor induced platelet aggregation. All hemolysin-negative bacteria except E. coli 536/21, without any adhesins, were able to activate protein kinase C reversibly but did not induce calcium influx. Activation of platelets with fluoride, an activator of the GTP-binding protein, was associated with protein kinase C activation, calcium influx, platelet aggregation, serotonin release, and 12-HETE formation. The simultaneous stimulation of platelets with NaF and the nonhemolytic E. coli strains suppressed several of the NaF-induced platelet responses. Membrane preparations isolated from stimulated platelets with hemolysin-negative and hemolysin-positive E. coli showed increased binding of guanylylimidodiphosphate, a nonhydrolyzable GTP analog, and enhanced GTPase activity.